Unearthing the Factors Behind Adoption of Electric Cars : An Indian Perspective - Chandel, Ajay (Indian Journal of Marketing, 2023)
Purpose : Electric cars have the potential to disrupt the existing automobile industry. Therefore, this study examined the factors influencing electric car adoption behavior among Indian car users. Methodology : Both exploratory and descriptive approaches were used to accomplish the stated objectives. The study was conducted in two phases. In phase one, a sample including 200 prospective electric car buyers was approached to understand the critical factors leading to adoption. In phase two, conjoint analysis was used to decipher the utilities drawn by 300 consumers from nine combinations of price, recharge time, and driving range as attributes selected after reviewing literature and an unstructured interaction with potential electric car buyers. Findings : The study indicated the three preferred combinations Indian consumers value the most when selecting an electric car. Practical Implications : Results could offer crucial information to decision-makers and producers of electric vehicles so they could introduce this cutting-edge technology into the Indian economy. The findings of this study, particularly the conjoint analysis, could be used by manufacturers to determine the relative relevance of features that increase utility. Originality : While the existing research was asymmetric and skewed toward understanding electric car adoption behavior in developed markets’ contexts, this study could decipher consumer behavior in relatively less discussed developing markets like India.